Assessment of the Quality of Life of Family Caregivers of Hemodialysis Patients with Chronic Kidney Disease in Yogyakarta - Pinasti Utami; Binar Sukma Cahyarni; Miranda Miranda; Bangunawati Rahajeng; Triana Arum Kusumaningtyas (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2026)
Chronic Kidney Disease (CKD) is a leading cause of mortality[A1.1][A1.2] in worldwide. In Indonesia, 713,783 cases were [A2.1][A2.2]reported, with 2,850 patients requiring hemodialysis, significantly impacting patients and requiring long-term care from family caregivers.[A3.1][A3.2] Despite the crucial role of family caregivers in supporting treatment adherence and patient well-being, studies examining caregivers’ quality of life in Indonesia, particularly in the Special Region of Yogyakarta, remain limited. This study assessed caregivers’ quality of life and its association with demographic factors in four hospitals, including three private and one public hospital located in Sleman, Yogyakarta City, and Bantul Regency. A cross-sectional multicenter study was conducted in four hospitals, involving 292 family caregivers. Data were collected using demographic questionnaires and WHOQOL-BREF, and analyzed with descriptive statistics and correlation tests. Most caregivers were 46–65 years old, female, had high school education, were not working, and were spouses of patients. Care duration ranged 13–36 months, with daily care exceeding 12 hours; patients underwent hemodialysis twice weekly. Quality of life was generally good in psychological and environmental domains, while physical and social domains ranged from moderate to good. [A4.1][A4.2]Significant correlations with caregivers’ quality of life were found in specific hospitals, including caregiver–family closeness (r = 0.294; p = 0.014), employment status (r = −0.256; p = 0.032), education level (r = 0.269; p = 0.021), and caregiving duration (r = −0.253; p = 0.025). These findings indicate that caregiver quality of life is influenced by both demographic and relational factors, highlighting the need for targeted support to maintain caregiver well-being and sustain patient care.